Problems of Development of Ecological Tourism in Uzbekistan and Possibilities of Their Solution - Azimovna, Musayeva Shoira (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In the article on given problems of development of ecological tourism and decision possibility, an estimation of potential of development of ecological tourism, perfection of the tourist legislation and questions of formation of strategy of development of ecological tourism in regions.